STUDENTS' EXPERIENCES IN REVIEWING LEARNING MATERIAL USING QUIZIZZ THROUGH PEER TEACHING APPROACH - Muhammad Dzimar; Ida Syarifa; Ahmad Burhanuddin (Journal of English Educational Study (JEES), 2026)
In today’s digital learning environment, integrating technology into the classroom has become essential to enhance student engagement and understanding. Quizizz, a gamified learning application, offers features such as instant feedback, varied question types, and competitive elements, making learning more interactive and enjoyable. Coupled with peer teaching, where students design questions and explain them to classmates, this method fosters deeper conceptual understanding, collaborative learning, and motivation. This study explores students' experiences in reviewing learning materials using the Quizizz platform through a peer teaching approach. Using a qualitative research design, data were collected through observation, documentation, and structured interviews with four English Education students at UIN K.H. Abdurrahman Wahid Pekalongan. The findings indicate that students responded positively to the use of Quizizz, describing it as fun, easy to use, and motivating. Peer-created quizzes contributed to a relaxed learning atmosphere, encouraging participation and focus. However, the study also identified several challenges, such as technical issues related to internet connectivity and difficulties in question design. Despite these obstacles, the integration of Quizizz with peer teaching is considered effective in enhancing engagement, promoting learner autonomy, and supporting meaningful learning experiences. This research offers insights into how gamified digital platforms, when combined with collaborative strategies, can support modern educational practices.Keywords: Digitaal learning, EFL classroom, Gamification, Peer teaching, Quizziz.